Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
Proceedings of the 2007 Conference on Future Play - Future Play '07 2007
DOI: 10.1145/1328202.1328215
|View full text |Cite
|
Sign up to set email alerts
|

Effective use of the periphery in game displays

Abstract: The human eye can perceive visual information with high acuity within a narrow foveal view; outside the foveal view (in the periphery), vision has progressively less resolution, and ability to perceive colour is reduced. In this paper, we argue that game displays can be improved by accounting for the part of the visual field in which information is displayed. We present two games in which information is visually encoded for presentation in the periphery. We conclude that the use of peripheral displays may be a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
(7 reference statements)
1
4
0
Order By: Relevance
“…Students working in the inner area had a larger number of neighbors and a larger number of objects present on the screen in the case of Ludic interactive activity, which prevented the player from having sufficient cognitive capacity to correctly process information on the screen. This result is consistent with Grad et al (2007) on the use of peripheral vision in video games, which indicate that the peripheral information can worsen the use of technological resources.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Students working in the inner area had a larger number of neighbors and a larger number of objects present on the screen in the case of Ludic interactive activity, which prevented the player from having sufficient cognitive capacity to correctly process information on the screen. This result is consistent with Grad et al (2007) on the use of peripheral vision in video games, which indicate that the peripheral information can worsen the use of technological resources.…”
Section: Discussionsupporting
confidence: 88%
“…3 and 4). Being visual information, the human eye perceives visual information simultaneously within a focal vision (looking at an object directly, capturing an image on the retina) and beyond (which surrounds the object with a lower resolution) (Grad, Graham, & Stewart, 2007). Thus, the focal information that the students consider while working, is located within their work space, and the rest of the elements in the common display, which are not necessary for the student activity and correspond to peripheral information.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The additional objects all moved around the scene at a constant speed and did little to attract the participants' attention. Grad et al [10] have shown that users tend not to notice peripheral information unless it is flashing or animated. Thus, we believe it is likely that the objects we added to the scene did not cause the participants to shift their focus away from the pink ship.…”
Section: Discussionmentioning
confidence: 99%
“…Peripheral vision is generally considered for display of information that can be detected without a priori focus, in games [13] and other areas of HCI, for example, deliver notifications without disrupting the task in focus [25] (e.g., keeping the eyes on the road while driving [18]). Recently, Luyten et al proposed a near-eye display for presentation of peripheral information that is positioned relative to the user's eyes such that it is impossible to focus on it [28].…”
Section: Peripheral Visionmentioning
confidence: 99%